The high mountains of Portugal [compact disc, unabridged] : a novel - Martel, Yann (Books on Tape ; Penguin Random House, 2016)
In Lisbon in 1904, a young man named Tomás discovers an old journal. It hints at the existence of an extraordinary artifact that, if he can find it, would redefine history. Traveling in one of Europe's earliest automobiles, he sets out in search of this strange treasure. Thirty-five years later, a Portuguese pathologist devoted to the murder mysteries of Agatha Christie finds himself at the center of a mystery of his own and drawn into the consequences of Tomás's quest.